Mulitdimensional progress : well-being beyond income - regional human development report for Latin America and the Caribbean : executive summary (UNDP New YorkUS, 2016)
Focuses on the increasingly pressing challenges facing the region - eradicating poverty and reducing inequalities in all its dimensions.
Keywords: HUMAN DEVELOPMENT